'I am the nurse who does io!': impact of a 'training of trainers' paediatric resuscitation training programme in malawi. (4th April 2011) - Pollock, L; Jefferis, O; Dube, Q; Kadewa, R
Abstract : Aims: To determine the impact of a single 'training of trainers' ETAT (Emergency triage, assessment and treatment) paediatric resuscitation training programme on clinical practice of participating healthcare workers in Malawi. Methods: Training was based on the WHO ETAT programme. Participants, senior healthcare workers working directly with children, completed a 4-day course including local ETAT implementation planning workshop. Impact on participant knowledge was assessed by pre and post-course test scores. Clinical practice impact was based on structured interview and retrospective case reporting at 6 months. Service impact was assessed after 6 months by site visits and hospital reports. Results: 79 participants (47 nursing staff, 27 clinical officers, 3 medical assistants, 2 doctors) from 25 hospitals in 18 Malawian healthcare districts were trained. Pre and post-course knowledge tests (n=79) showed improvement in both individual and overall scores (overall mean score pre: 10.27 post: 12.48 p=<0.001). At 6 month follow-up 17 hospitals were visited and 20 made progress reports. Contact was lost with 5 hospitals. Around 25% of participants had left paediatric or health services. 6 month post-course knowledge test (n=32) showed retained improvement compared to pre-course scores (mean 6 month score: 11.81, p=0.001). 26 participants completed a structured interview at 6 months. All attributed positive changes in clinical practice to the course. 41 specific case histories of children's lives saved attributed to skills not used prior to the course were reported. 'Life-saving' skills included intra-osseous access (30 cases), bag-valve mask ventilation (7 cases) and anti-convulsant protocols (4 cases). 20 hospitals reported impact on service. 3 hospitals had introduced triage, 14 made improvements to existing triage systems. 8 hospitals had established a specific clinical area for resuscitation of children. 11 hospitals had obtained funding for participants to train colleagues: a further 272 healthcare workers had been trained in triage skills. Conclusions: Logistical difficulties, resource limitation and high staff turnover were barriers to both local implementation of ETAT and assessment at follow-up. Training programmes and 'real-life' implementation need to be continuously supported to sustain improvement. Despite this there was evidence of knowledge gained and retained, and most importantly of positive impact on outcome for individual children. True impact may be underestimated.